Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) ta có: (-32)9 = [(-2)5 ]9 = (-2)45 = - (2)45
(-16)13 = - [ 24 ]13 = - (2)52
=> ....
b) ta có: (-5)30 = 530 = (53)10 = 12510
(-3)50 = 350 = (35)10 = 24310
=> ....
c) ta có: (-32)9 = (-2)45 = (-2)13 . 232
(-18)13 = [(-2).32 ]13 = (-2)13 . 339
=> ....
d) ta có: \(\left(-\frac{1}{16}\right)=-\left(\frac{1}{2}\right)^4.\)
\(\left(-\frac{1}{2}\right)=-\left(\frac{1}{2}\right)^1< -\left(\frac{1}{2}\right)^4\)
b) \(9^5=3^{2\cdot5}=3^{10}\)
\(27^3=3^{3\cdot3}=3^9\)
=> tự kết luận
c) \(\left(\frac{1}{8}\right)^6=\left(\frac{1}{2}^3\right)^6=\left(\frac{1}{2}\right)^{18}\)
\(\left(\frac{1}{32}\right)^4=\left(\frac{1}{2}^5\right)^4=\left(\frac{1}{2}\right)^{20}\)
=> tự kết luận
b) Ta có: \(9^5=\left(3^2\right)^5=3^{10}\)
\(27^3=\left(3^3\right)^3=3^9\)
Vì 10 > 9 => 310 > 39
Vậy 95 > 273
1. So sánh :
b) 9^5 và 27^3
9^5 = ( 3^2 )^5 = 3^10
27^3 = ( 3^3 )^3 = 3^9
Vì 3^10 > 3^9 => 9^5 > 27^3
Vậy 9^5 > 27^3
c) \(\left(\frac{1}{8}\right)^6\)và \(\left(\frac{1}{32}\right)^4\)
\(\left(\frac{1}{8}\right)^6=\left(\frac{1}{2}\right)^{3.6}=\left(\frac{1}{2}\right)^{18}\)
\(\left(\frac{1}{32}\right)^4=\left(\frac{1}{2}\right)^{5.4}=\left(\frac{1}{2}\right)^{20}\)
Vì ( 1/2)^18 < (1/2)^20 => (1/8)^6 < (1/32)^4
Vậy (1/8)^6 < (1/32)^4
a, Có : (1/60)^200 = [(1/2)^4]^200 = (1/2)^800
Vì 0 < 1/2 < 1 nên (1/2)^800 > (1/2)^1000
=> (1/16)^200 > (1/2)^1000
Tk mk nha
Bài giải
Ta có : \(9^{99}=\left(9^{11}\right)^9\)
Vì \(\left(9^{11}\right)^9>99^9\text{ }\left[\left(81\cdot9^9\right)^9>99^9\right]\text{ }\Rightarrow\text{ }9^{99}>99^9\)
Ta có (-32)27 = -3227 = -(25)27 = -25.27 = -2135 = - 296.239
(-18)39 = -1839 = -(2.9)39 = -239.(32)39 = -239.378
Nhận thấy 296 = (23)32 = 832 < 932 = (32)32 = 364 < 378
=> 296 < 378
=> -296 > -378
=> - 296.239 > -239.378
=> (-32)27 > (-18)39